Negotiating Local Wisdom in School Management: An Ethnographic Study of Value Internalization and Cultural Tensions in Education - Nanik Hindaryatiningsih; Farida Ariyani; Fina Amalia Masri; Ansor Putra; Rusdiyana Tugy; Sabrin Sabrin; Yuniyarti Ahiri; Jamal Harimudin (Jurnal Pendidikan Progresif, 2026)
This study aims to critically examine how Butonese local wisdom values are internalized within school management practices and how these values are negotiated in response to modern educational and socio-cultural dynamics.  This study employed a qualitative approach with a critical ethnographic design. Data were collected through prolonged participant observation, in-depth semi-structured interviews with key informants (principals, teachers, students, and community leaders), and document analysis. Data were analyzed using an interactive model involving thematic coding, categorization, and interpretation. The findings indicate that local wisdom values such as gau and pombala (deliberation), poromu inda posaangu (collectivity), and tuturakana sara (honesty and justice) are institutionally embedded in school management processes. However, the internalization of these values does not occur linearly but is shaped through ongoing negotiations between institutional expectations and the realities of students' lives. Tensions arise especially when students face the conflicting influences of digital culture and the social environment, resulting in adaptive, selective, and sometimes resistant behaviors aligning with cultural norms. This study highlights that value internalization is a dynamic socio-cultural process, not a fixed outcome. Schools function not only as transmitters of cultural values but also as mediating spaces where local and global values are negotiated. This study contributes to broadening the understanding of culturally responsive character education by emphasizing the importance of adaptive, context-sensitive strategies. Keywords: buton society, character education, cultural negotiation, ethnography. local wisdom.